The European Union’s Legal Framework on the Member State’s Margin of Appreciation in Land Policy – The CJEU’s Case Law After the “KOB” SIA Case - Korom, Ágoston (Acquisition of Agricultural Lands, 2022)
Several studies and scientific workshops have considered the member states’ rules—within the framework of EU law—on the ownership and use of agricultural and forest property, taking into account that this area is significant not only for the member states that acceded after 2004, such as Hungary, but also for the founding members. These examinations have focused on the public interests acknowledged by the Court of Justice of the European Union (CJEU), such as the preservation of the rural population; the promotion of small and middle-sized, livable properties; and the easing of the speculative pressure on the land market, which should be achieved in practice without compromising EU law—especially its fundamental freedoms. This characteristic of the CJEU’s relevant case law primarily led to the application of the free movement of capital; nevertheless, the CJEU’s judgment in the “KOB” SIA case resulted in a significant change in this area, which is the main subject of the current examination. Keywords: Member state’s margin of appreciation in land policy, free movement of capital, targets of the CAP in the land policy, legal development in the KOB SIA case, freedom of establishment, Services Directive